The Effect of the Nusantara Capital City Authority on East Kalimantan’s Regional Autonomy: A Constitutional Analysis - Nanik Prasetyoningsih; Cyabriena Asela; Rajali Haji Aji (Constitutionale, 2025)
Law Number 3 of 2022 on the Nusantara Capital City has sparked constitutional debate, particularly regarding its effects on regional autonomy in East Kalimantan. The debate centers on the extensive authority granted to the Nusantara Capital City Authority, which functions outside the conventional framework of decentralized local governance. This study evaluates whether the NCCA’s legal structure and powers align with the constitutional principles of decentralization set out in Article 18 of the 1945 Constitution. Through normative legal research using statutory and conceptual approaches, the study finds that the NCCA’s governance model diverges from democratic local governance standards due to the absence of a regional legislative council and an elected regional head. Consequently, the establishment of the NCCA has effectively reduced the autonomous authority of the East Kalimantan provincial government. The study recommends instituting a regular constitutional review mechanism to ensure alignment between national strategic priorities and regional autonomy.